COOL-LAMPS. VII. Quantifying Strong-lens Scaling Relations with 177 Cluster-scale Strong Gravitational Lenses in DECaLS - Simon D. Mork; Michael D. Gladders; Gourav Khullar; Keren Sharon; Nathalie Chicoine; Aidan P. Cloonan; Håkon Dahle; Diego Garza; Rowen Glusman; Katya Gozman; Gabriela Horwath; Benjamin C. Levine; et al. (The Astrophysical Journal)
We estimate the Einstein-radius-enclosed total mass for 177 cluster-scale strong gravitational lenses identified by the ChicagO Optically selected Lenses Located At the Margins of Public Surveys (COOL-LAMPS) collaboration with lens redshifts ranging from 0.2 ⪅ z ⪅ 1.0 using the brightest-cluster-galaxy (BCG) redshift and an observable proxy for the Einstein radius. We constrain the Einstein-radius-enclosed luminosity and stellar mass by fitting parametric spectral energy distributions to aperture photometry from the Dark Energy Camera Legacy Survey (DECaLS) in the g -, r -, and z -band Dark Energy Camera filters. We find that the BCG redshift, enclosed total mass, and enclosed luminosity are strongly correlated and well described by a planar relationship in 3D space. We find that the enclosed total mass and stellar mass are correlated with a logarithmic slope of $0.50{0}_{-0.031}^{+0.029}$ , and the enclosed total mass and stellar-to-total mass fraction are correlated with a logarithmic slope of $-0.49{5}_{-0.033}^{+0.032}$ . In tandem with the small radii within which these slopes are constrained, this may suggest invariance in baryon conversion efficiency and feedback strength as a function of cluster-centric radii in galaxy clusters. Additionally, the correlations described here should have utility in ranking strong-lensing candidates in upcoming imaging surveys—such as Rubin/Legacy Survey of Space and Time—in which an algorithmic treatment of strong lenses will be needed due to the sheer volume of data these surveys will produce.